The Impact of E-Learning on Adherence to Guidelines for Acute Gastroenteritis: A Single-Arm Intervention Study - (:unkn) unknown (PUBLIC LIBRARY SCIENCE, 2015)
Objective E-learning is a candidate tool for clinical practice guidelines (CPG) implementation due to its versatility, universal access and low costs. We aimed to assess the impact of a five-module e-learning course about CPG for acute gastroenteritis (AGE) on physicians' knowledge and clinical practice. Study design This work was conceived as a pre/post single-arm intervention study. Physicians from 11 European countries registered for the online course. Personal data, pre- and post-course questionnaires and clinical data about 3 to 5 children with AGE managed by each physician before and after the course were collected. Primary outcome measures included the proportion of participants fully adherent to CPG and number of patients managed with full adherence. Results Among the 149 physicians who signed up for the e-learning course, 59 took the course and reported on their case management of 519 children <5 years of age who were referred to their practice because of AGE (281 and 264 children seen before and after the course, respectively). The course improved knowledge scores (pre-course 8.6 +/- 2.7 versus post-course 12.8 +/- 2.1, P < 0.001), average adherence (from 87.0 +/- 7.7% to 90.6 +/- 7.1%, P = 0.001) and the number of patients managed in full adherence with the guidelines (from 33.6 +/- 31.7% to 43.9 +/- 36.1%, P = 0.037). Conclusions E-learning is effective in increasing knowledge and improving clinical practice in paediatric AGE and is an effective tool for implementing clinical practice guidelines.
Keywords: RANDOMIZED CONTROLLED-TRIAL; EVIDENCE-BASED MEDICINE; PEDIATRIC GASTROENTERITIS; EMERGENCY-DEPARTMENT; ACUTE DIARRHEA; PRIMARY-CARE; CHILDREN; MANAGEMENT; IMPLEMENTATION; RESUSCITATION